The short-term effectiveness of a remedial mathematics course: Evidence from a UK university - Giorgio Di Pietro (Institute for the Study of Labor (IZA), 2012)
Whilst in the US there is a growing debate about the effectiveness of remedial university courses, this issue is less questioned in the UK. Using a regression discontinuity approach and data from a large School of a post-1992 UK university, we estimate the effect of remediation on student outcomes. We find no evidence that attending a math remedial program improves student performance in the first year. This finding is consistent and complements that of a recent study by Lagerlöf and Seltzer (2009), which is based on data from a pre-1992 UK university. Taken together, these results may call for a review of the remediation policy offered at university level in the UK.
urn:nbn:de:101:1-201205026593
Keywords: A22; I20; 330; regression discontinuity design; remedial mathematics; student performance; Studierende; Unterricht; Bildungsniveau; Großbritannien